Pendidikan dan pelatihan bantuan hidup dasar (BHD) untuk meningkatkan pengetahuan dan keterampilan remaja: A literature review - Arparitna, Ketut Yudi; Uly, Nilawati; Alim, Andi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Basic Life Support (BLS) is a crucial skill for managing emergencies such as sudden cardiac arrest. BLS, initiated in adolescence, is believed to improve individual and community preparedness in responding to emergencies. However, the effectiveness of various training methods remains debated. Purpose: To examine the effectiveness of BLS education and training in improving adolescent knowledge and skills. Method: This literature review examined 19 articles published between 2012 and 2025. Articles were obtained from Scopus, the Directory of Open Access Journals (DOAJ), and Google Scholar. Data were analyzed descriptively and qualitatively based on intervention methods, learning outcomes, and the sustainability and limitations of BLS training. Results: Lectures and simulations were effective in improving student knowledge and skills. Innovative approaches, such as audiovisual media, flipped classrooms, and virtual reality, also demonstrated positive results, particularly in psychomotor and affective aspects. However, skill retention tends to decline 3–6 months post-training if there is no further reinforcement. General limitations of the study include a narrow sample size, lack of long-term evaluation, and limited practical tools. Conclusion: Basic Life Support (BLS) education and training have proven effective, but its success is greatly influenced by program sustainability, infrastructure support, and active participant engagement. Curriculum integration, regular retraining, and further research with longitudinal designs are needed to ensure the long-term impact of BLS training on adolescents. Keywords: Adolescents; Basic Life Support (BLS); Education and Training; Knowledge; Skills. Pendahuluan: Bantuan Hidup Dasar (BHD) merupakan keterampilan penting dalam penanganan kondisi gawat darurat seperti henti jantung mendadak. BHD yang dimulai sejak usia remaja, diyakini mampu meningkatkan kesiapsiagaan individu dan komunitas dalam merespons kejadian darurat. Namun, efektivitas metode pelatihan yang beragam masih menjadi perdebatan. Tujuan: Untuk mengkaji efektivitas pendidikan dan pelatihan bantuan hidup dasar (BHD) dalam meningkatkan pengetahuan dan keterampilan remaja. Metode: Penelitian tinjauan literatur terhadap 19 literatur yang diterbitkan antara tahun 2012-2025. Artikel diperoleh dari basis data Scopus, directory of open access journals (DOAJ), dan Google Scholar. Data dianalisis secara deskriptif-kualitatif berdasarkan metode intervensi, capaian pembelajaran, serta aspek keberlanjutan dan keterbatasan pelaksanaan pelatihan BHD. Hasil: Metode ceramah dan simulasi efektif dalam meningkatkan pengetahuan dan keterampilan siswa. Pendekatan inovatif, seperti media audiovisual, flipped classroom, dan virtual reality juga memperlihatkan hasil positif, khususnya dalam aspek psikomotorik dan afektif. Namun, retensi keterampilan cenderung menurun dalam 3–6 bulan pasca pelatihan jika tidak ada penguatan lanjutan. Keterbatasan umum dalam studi meliputi cakupan sampel yang sempit, kurangnya evaluasi jangka panjang, serta keterbatasan alat praktik. Simpulan: Pendidikan dan pelatihan BHD terbukti efektif, tetapi keberhasilannya sangat dipengaruhi oleh kesinambungan program, dukungan infrastruktur, dan keterlibatan aktif peserta. Diperlukan integrasi kurikulum, pelatihan ulang berkala, serta riset lanjutan dengan desain longitudinal untuk menjamin dampak jangka panjang pelatihan BHD pada remaja. Kata Kunci: Bantuan Hidup Dasar (BHD); Keterampilan; Pendidikan dan Pelatihan; Pengetahuan; Remaja.